Detectability of Self-lensing Flares of White Dwarfs with Compact Companions - Guy Nir; Joshua S. Bloom (The Astrophysical Journal)
Binaries containing compact objects, viewed nearly edge on, can produce periodic brightening events under certain conditions on the masses, radii, and binary separation. Such flares are caused by one object gravitationally lensing another, in what is known as self-lensing flares . We present a simulation tool that efficiently reproduces the main features of self-lensing flares and facilitates a detection sensitivity analysis for various sky surveys. We estimate the detection prospects for a handful of representative surveys when searching for systems of either two white dwarfs or a white dwarf with other compact objects, i.e., neutron stars and black holes. We find only a marginal ability to detect such systems in existing surveys. However, we estimate many such systems could be detectable by surveys in the near future, including the Vera Rubin Legacy Survey of Space and Time (LSST). We provide a quantitative analysis of the detectability of double-compact object self-lensing flares across the landscape of system parameters, and a qualitative discussion of survey and follow-up approaches to distinguish such flares from confounding events, such as stellar flares, satellite glints, and cosmic rays. We estimate 0.3, 3 and 247 double white dwarf systems could be detected by Transiting Exoplanet Survey Satellite, Zwicky Transient Facility, and LSST, respectively. A similar number of systems with a neutron star or black hole companion could be detected, but we caution that the number densities of such binaries is model dependent and so are our detection estimates. Such binaries can be used to constrain models of the end states of binary evolution.